Identifikasi Cagar Budaya di Kota Depok sebagai Upaya dalam Membangun Kesadaran Sejarah Masyarakat - Absor, Nur Fajar; Wahyudin; Santosa, Yusuf Budi Prasetya; Abdillah, Nur Ramadhani (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
Within the scope of urban history there are 4 periods, namely prehistoric, traditional, colonial, and modern. One of the cities that has historical heritage, either in the form of buildings or building structures is Depok City. Depok during the colonial period was an area of ​​Gementee Bestuur which was given the freedom to manage its own territory. Therefore, in Depok City there are many relics of the colonial period identified as cultural heritage, but not all Depok people know that Depok has a long history of cultural heritage in its area. Meanwhile, the objectives of this study are (1) to identify the cultural heritage in Depok City; and (2) to analyze efforts to build public historical awareness through the identification of cultural heritage in Depok City. The research method used in this research is descriptive qualitative. The results of this study found that there are 21 cultural heritages in Depok City. To raise awareness of history in the Depok community through the identification of cultural heritage, it can be done by (1) incorporating the introduction of the cultural heritage of the City of Depok into the local content; (2) conduct socialization on various cultural heritages in Depok City; (3) make routine 'Depok Heritage Festival' activities; and (4) inserting a list of identified cultural heritages into the depok.go.id website.